Exploring the Direction for Developing Lifelong Education Program for the Hearing Impaired in G Metropolitan City - Lee, Jae-Ho; Lee, Woo-Jin (Journal of speech-language & hearing disorders, 2025)
Purpose: The purpose of this study is to investigate the current state and needs of lifelong education participation among individuals with hearing impairments. Methods: The study focused on the lifelong education status and needs of individuals with hearing impairments in G Metropolitan City. A total of 51 participants were selected through stratified sampling, and a focused group interview was conducted with three. Results: First, the survey on the participation status of lifelong education programs among individuals with hearing impairments in G Metropolitan City revealed that only 58.8% had participated in such programs. The main reasons for non-participation were a lack of information (45.0%), lack of time (30.0%), and lack of motivation (5.0%). The primary purposes of participating in lifelong education programs were for hobbies and leisure activities (40.6%), expanding opportunities for social participation (43.7%), and acquiring diverse information (31.2%). An analysis of satisfaction with lifelong education programs showed an average score of 3.67 ( .85). The highest-rated factors were staff attitudes toward individuals with disabilities (3.58), the convenience provided by lifelong education institutions (3.76), and instructors’ attitudes toward individuals with disabilities (3.68). Key factors identified for the future development of lifelong education included the development of dedicated lifelong education programs for individuals with disabilities (31.5%), financial support for programs (20.8%), and the provision of information on lifelong education institutions and programs (12.5%). Conclusions: Based on the study’s findings, lifelong education programs for individuals with hearing impairments should consider life stages and family relationships. Since the needs of adulthood, middle age, and old age differ, strategies must be tailored accordingly. specific social policy recommendations were made for individuals with hearing impairments and families. KCI Citation Count: 0